THE USE OF ZIRCONIA-BASED BIOMATERIALS IN DENTAL PROSTHETICS (Journal of Medical & Health Sciences Review, 2025)
Background: High strength, wear resistance, biocompatibility, and aesthetically pleasing properties make zirconia-based biomaterials popular in the application of dental prosthesis. Nevertheless, there are divergent professional perceptions and clinical experiences in working with various types of zirconia, which may impact the material and treatment choice as well as the outcome of patients.Objective: The aim is to assess the perceptions of dentists and dental specialists regarding dental zirconia-based biomaterials in aspects of durability, aesthetics, patient satisfaction, and recommendation, and to investigate how demographic factors and career aspects affect those perceptions.Methods: This was a Cross-sectional survey on dental professionals, which gathered data about demographics, clinical utilization patterns, and preferences of the zirconia type and performance assessment. Cronbach's Alpha was used to analyze reliability. Chi-Square tests compared variables of a categorical nature. The mean ratings were compared between groups using One-way ANOVA and independent sample t -t-tests. Pearson correlation evaluated connections between durability, aesthetics, and satisfaction variables with recommendations. There were predictors of patient satisfaction using multiple linear regression.Results: There was excellent internal consistency reliability (Cronbach's Alpha = 0.998). Chi-Square tests indicated that there were significant relationships between Gender and Zirconia Type (p < 0.001), between Specialization and Primary Application (p = 0.027). ANOVA identified that Durability Ratings among the Zirconia Types differed significantly (p < 0.001), Aesthetic Ratings among the Specializations differed significantly (p < 0.001), and that Patient Satisfaction among the Usage Frequencies differed significantly (p < 0.001). The gender variance was significant in terms of durability rating and aesthetic (p < 0.001). Very good correlations were recorded between durability, aesthetics, satisfaction, and recommendation (r = 0.824-0.902). A regression analysis indicated that Durability (beta = 0.677, p < 0.001) and Aesthetics (beta = 0.213, p < 0.001) were considered significant predictors of patient satisfaction, and experience was not.Conclusion: The durability and aesthetics of zirconia are the most influential factors of patient satisfaction, which override the experience of practitioners. The gender, specialization, and frequency of use of materials selected and applied depend on the practitioner. These results underline the value of integrating the quality of material and clinical quality in order to improve prosthetic outcomes.